Perancangan Sistem Informasi Pos Untuk Toko Devanda Dengan Basis Client Server - Priyadi, Priyadi; Priyadi, Agus; Santoso, Lukman; Ati Suryana, Dinda (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
This research begins with data collection through a combination of interview, observation, and literature study techniques. The problem analysis found was the slow sales service and purchase process at the store. The further impact is customer disappointment and the use of more time and energy resources. The solution offered in this research is the design of a computer-based information system that integrates workflow and optimal utilization of client server-based computer technology. The analysis in this study is presented in the form of a flowchart of the new system to be developed and analysis of the data structure using the Entity Relationship Diagram technique. Then the design results are presented in the form of a representative form design with workflow analysis described in the analysis and deployment diagram that illustrates how the system will be distributed with a client server computer technology approach. In conclusion, it is explained that the new system proposed in this design has been successfully presented logically, systematically, and easily developed into an integrative and systematic software project.